Structural health monitoring of GFRP laminates using graphene-based smart strain gauges - (:unkn) unknown (SPRINGER HEIDELBERG, 2018)
Graphene nanocomposites are constantly being explored for their applicability in the growing domain of strain monitoring (Jing et al. in Chin Phys B 22(5):057701, 2013) for real-time health and integrity assessment of structural parts. Strain gauges were manufactured by incorporating conductive graphene nanoplatelets (GNPs) in insulating polystyrene matrix by varying filler concentrations. Initial measurements showed that the resistance of these gauges decreases with increasing content of GNPs. For structural health monitoring (SHM) applications, these gauges were pasted on laminated glass fiber composite substrate. The specimens with integrated gauges were tested under monotonic tensile loading. The piezoresistive response of gauges was observed and registered as a means to detect strains in the composite specimens. The results presented in this paper demonstrate SHM capabilities of these smart strain gauges.
Keywords: Nanostructures; Smart materials; Layered structures; Mechanical testing; Structural health monitoring; CARBON-BLACK; ELECTRICAL-RESISTANCE; COMPOSITE; FIBER; DAMAGE; LAYER; PIEZORESISTIVITY; NANOCOMPOSITES; COMPRESSION; BEHAVIOR